1999
DOI: 10.2307/3434427
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Environmental Tobacco Smoke Exposure

Abstract: Biomarkers are desirable for quantitating human exposure to environmental tobacco smoke (ETS) and for predicting potential health risks for exposed individuals. A number of biomarkers of ETS have been proposed. At present cotinine, measured in blood, saliva, or urine, appears to be the most specific and the most sensitive biomarker. In nonsmokers with significant exposure to ETS, cotinine levels in the body are derived primarily from tobacco smoke, can be measured with extremely high sensitivity, and reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 29 publications
2
127
0
2
Order By: Relevance
“…A direct physical measurement of exposure to tobacco smoke would reduce potential problems associated with self-report, such as inaccurate recall, underreporting, and misinterpretation of questions. In the present study, serum cotinine have been selected because other markers (e.g., carbon monoxide, cyanide, nicotine-derived nitrosoamines) are non-specific, insensitive, technically demanding or have high baseline values even in non-smokers (Benowitz et al 1999). Nonsmokers exposed to typical levels of ETS have cotinine levels of less than 1 ng/mL, with heavy exposure to ETS producing levels in the1-15 ng/mL range (NCEH 2003), in the present study too, both the passive and controls subjects were selected in the above estimated range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct physical measurement of exposure to tobacco smoke would reduce potential problems associated with self-report, such as inaccurate recall, underreporting, and misinterpretation of questions. In the present study, serum cotinine have been selected because other markers (e.g., carbon monoxide, cyanide, nicotine-derived nitrosoamines) are non-specific, insensitive, technically demanding or have high baseline values even in non-smokers (Benowitz et al 1999). Nonsmokers exposed to typical levels of ETS have cotinine levels of less than 1 ng/mL, with heavy exposure to ETS producing levels in the1-15 ng/mL range (NCEH 2003), in the present study too, both the passive and controls subjects were selected in the above estimated range.…”
Section: Resultsmentioning
confidence: 99%
“…Measuring cotinine is preferred over measuring nicotine because cotinine persists longer in the body. The average half life of cotinine in different body fluids in adults is approximately 20 h, compared with a half-life of 2 h for nicotine, making it a good indicator of the integrated exposure over the previous 2-3 days (Benowitz 1999;Rebagliato 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of nicotine metabolites in biological fluids (mainly blood and urine) has attracted more attention from the scientific community. The determination of cotinine, the major proximate metabolite of nicotine, has been widely used by scientist to evaluate ETS exposure given that this substance reflects exposure to nicotine, which is almost specific to tobacco [6]. Nicotine-derived nitrosoamines such as 4-(methylnitrosoamino)-1-(3-pyridyl)-1-butanone (NNK) have also been proposed [7].…”
mentioning
confidence: 99%
“…Likewise, a 20-year prospective analysis of the British Regional Heart Study [6•] found that SHS exposure as measured by serum cotinine concentrations [29] at baseline was associated with a greater excess risk of CHD (OR, 1.45-1.57) than that estimated by previous investigators, who relied only upon partner smoking history for assessment of SHS exposure. This study was conducted in the United Kingdom, where a legislation requiring smoke-free public settings (eg, restaurants, pubs) has been implemented only recently (July 2007).…”
Section: Epidemiologic Evidencementioning
confidence: 98%